Household Air Pollution and Respiratory Health in Rural Crete, Greece: A Cross-Sectional FRESH AIR Study - Marilena Anastasaki (MDPI AG, 2021)
Breathing polluted air is a risk to respiratory conditions. During the Greek financial crisis, the use of household fireplaces/wood stoves shifted from mostly decorative to actual domestic heating, resulting in increased indoor smoke production. We aimed to evaluate household air pollution (HAP), fuel use and respiratory symptoms in rural Crete, Greece. PM2.5 and CO were measured in 32 purposively selected rural households (cross-sectional study) at periods reflecting lesser (baseline) versus extensive (follow-up) heating. Clinical outcomes were assessed using questionnaires. Mean PM2.5 were not significantly different between measurements (36.34 µg/m3 vs. 54.38 µg/m3, p = 0.60) but exceeded the WHO air quality guidelines. Mean and maximal CO levels were below the WHO cut-offs (0.56 ppm vs. 0.34 ppm, p = 0.414 and 26.1 ppm vs. 9.72 ppm, p = 0.007, respectively). In total, 90.6% of households were using wood stoves or fireplaces for heating, but half also owned clean fuel devices. The differences between devices that were owned versus those that were used were attributed to financial reasons. In both cases, the most frequent respiratory symptoms were phlegm (27.3% vs. 15.2%; p = 0.34) and cough (24.2% vs. 12.1%; p = 0.22). Our findings demonstrate the magnitude of HAP and confirm the return to harmful practices during Greece’s austerity. Upon validation, these results can support strategies for fighting fuel poverty, empowering communities and strengthening local health systems.